A study to evaluate the Effect of Carburization on LM13 Aluminium alloy –Quartz Composites - A. Hiremath, Anupama; ., . (International Journal of Engineering and Technology, 2018)
Aluminum metal matrix composites have emerged as a new-class of lightweight, high-strength materials that are employed extensively in the automobile industries. Under such operating conditions, the material is constantly exposed to severe carbonaceous environment. The current paper investigates the effect of carburization on the chilled aluminium alloy reinforced with quartz particles. The composite is cast with the aid of mild steel, copper (metallic chills), silicon carbide and graphite (non-metallic) end chills by varying the weight percent quartz reinforcement. The variation in weight percent of reinforcement ranges from 5 to 15 percent with 5 percent increment in every iteration. Stir casting method of fabrication is employed to ensure even distribution of reinforcement within the matrix. The specimens are drawn from near chill end to evaluate the effect of chills on the soundness of the casting. The specimens are subjected to pack carburization for 60, 90 and 120 hours.
Keywords: Aluminium matrix composites; AlSi alloys; carburization; chills; quartz; stir casting